2011
DOI: 10.1016/j.ccr.2011.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Feedback Regulation of PI3K and Androgen Receptor Signaling in PTEN-Deficient Prostate Cancer

Abstract: Summary Prostate cancer is characterized by its dependence on androgen receptor and frequent activation of PI3K signaling. We find that AR transcriptional output is decreased in human and murine tumors with PTEN deletion and that PI3K pathway inhibition activates AR signaling by relieving feedback inhibition of HER kinases. Similarly, AR inhibition activates AKT signaling by reducing levels of the AKT phosphatase PHLPP. Thus, these two oncogenic pathways cross-regulate each other by reciprocal feedback. Inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

74
1,016
6
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,059 publications
(1,101 citation statements)
references
References 44 publications
74
1,016
6
5
Order By: Relevance
“…The PI3K/AKT pathway is inhibited by phosphatase and tensin homolog (PTEN), which is a tumor suppressor 35. A previous study reported that complete loss of the PTEN gene is more frequent in high‐grade prostate cancer,36 in which, the PI3K/AKT pathway is constitutively active and requires minimal activation by IGF‐1 or other hormones.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT pathway is inhibited by phosphatase and tensin homolog (PTEN), which is a tumor suppressor 35. A previous study reported that complete loss of the PTEN gene is more frequent in high‐grade prostate cancer,36 in which, the PI3K/AKT pathway is constitutively active and requires minimal activation by IGF‐1 or other hormones.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases the biomarker rationale for AKT inhibitor synergy with RTK or MAPK inhibition was less direct and indicative of crosstalk and feedback signaling previously reported 31 . Interestingly antagonism was observed in cell lines harboring activating mutations of AR [32][33][34][35] . Feedback signaling resulting from AKT inhibition has been seen to drive AR activity which in turn can lead to the activation of the MAPK cascade 35,36 , attenuating respectively targeting drug activity.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal cycling conditions were as follows: 95 C for 20 seconds followed by 40 cycles of 95 C for one second and 60 C for 20 seconds. To quantify the miRNA expression in the tumor tissues, we used the relative quantification (DDCt) method (13) with RNU6b serving as an internal control. RNA from PNF or LNCaP cells was always analyzed in parallel on the same reaction plate, and the expression of examined miRNAs in PNF or LNCaP cells was arbitrarily set to one.…”
Section: Mirna Qrt-pcrmentioning
confidence: 99%
“…The Pleckstrin homology domain and leucine rich repeat protein phosphatase (PHLPP) enzymes dephosphorylate the AKT kinase, which, in the phosphorylated state, induces cell growth. Loss of, or reduction of, PHLPP1 or PHLPP2 and the ensuing increase in phosphorylation of AKT is an established cause for induction and/or progression of prostate carcinoma (11)(12)(13). MiR-15a and miR-375, therefore, play important roles in prostate carcinoma and may represent potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%